Comparative Analysis of Islamic Economics with Capitalism - Chandra; Sofyan Al-Hakim; Iwan Setiawan (al-Afkar, Journal For Islamic Studies, 2023)
This research discusses the concept of the Islamic economic system. The main objective of this study is to determine the relationship between Islam and the economy and how the pattern of Islamic regulation in the economic field, then the regulation of individuals in obtaining wealth. Is it true that the Islamic economic system is the only economic theory that can be expected as a light in the face of economic problems is an economic system that is able to create justice, the welfare of all parties, and the blessings of the world and the here after. Islamic economics in practice is inseparable from Islamic economic law. Islamic economic law that underlies the economic system is very different from the capitalist economic system.